Cardiovascular Disease in Ageing: An Overview on Thoracic Aortic Aneurysm as an Emerging Inflammatory Disease - Pisano, Calogera; Balistreri, Carmela Rita; Ricasoli, Alessandro; Ruvolo, Giovanni (Mediators of Inflammation, 2017)
Medial degeneration associated with thoracic aortic aneurysm and acute aortic dissection was originally described by Erdheim as a noninflammatory lesion related to the loss of smooth muscle cells and elastic fibre fragmentation in the media. Recent evidences propose the strong role of a chronic immune/inflammatory process in aneurysm evocation and progression. The coexistence of inflammatory cells with markers of apoptotic vascular cell death in the media of ascending aorta with aneurysms and type A dissections raises the possibility that activated T cells and macrophages may contribute to the elimination of smooth muscle cells and degradation of the matrix. On the other hand, several inflammatory pathways (including TGF-β, TLR-4 interferon-γ, chemokines, and interferon-γ) seem to be involved in the medial degeneration related to aged and dilated aorta. This is an overview on thoracic aortic aneurysm as an emerging inflammatory disease.